Probability of default as the early warning system for the Indonesian banking sector - Ari Christianti (University of Merdeka Malang, 2019)
Early Warning System for banks is used to predict default risk. This research is to test the probability of defaults with the probability of default in the real condition of banks. The probability of default risk is measured by KMV-Merton Model and the probability of default in the real condition of banks is bank’s performance based on whether there are bank’s actions that cause changes in the bank's financial statements report. This study using banks listed in the Indonesian Stock Exchange (IDX) from 2010-2015. This study analysis probability of default with financial condition based from 4 commercial bank categories and BUKU (Commercial Bank Based on Business Activities) categories. The results of this study are the probability of default with Merton model give a strong signal against the default of bank for one bank only but for banks in BUKU 4 give a strong signal that banks in this category do not default. Since for other banks and for other BUKU categories do not represent the real condition from the probability of default. It can be concluded that the Merton model is not generated sufficient enough model to predict the probability of default since it assumes that the market is in under efficient condition, and it just considers firm-specific risk.JEL Classification: G21, G32, G33DOI: https://doi.org/10.26905/jkdp.v23i2.2856